HIV‐1 Tat C modulates NOX2 and NOX4 expressions through miR‐17 in a human microglial cell line - Jadhav, Vaishnavi Sunil; Krause, Karl‐Heinz; Singh, Sunit K. (Journal of neurochemistry, 2014)
HIV‐1 invades CNS in the early course of infection, which can lead to the cascade of neuroinflammation. NADPH oxidases (NOXs) are the major producers of reactive oxygen species (ROS), which play important roles during pathogenic insults. The molecular mechanism of ROS generation via microRNA‐mediated pathway in human microglial cells in response to HIV‐1 Tat protein has been demonstrated in this study. Over‐expression and knockdown of microRNAs, luciferase reporter assay, and site‐directed mutagenesis are main molecular techniques used in this study. A significant reduction in miR‐17 levels and increased NOX2, NOX4 expression levels along with ROS production were observed in human microglial cells upon HIV‐1 Tat C exposure. The validation of NOX2 and NOX4 as direct targets of miR‐17 was done by luciferase reporter assay. The over‐expression and knockdown of miR‐17 in human microglial cells showed the direct role of miR‐17 in regulation of NOX2, NOX4 expression and intracellular ROS generation. We demonstrated the regulatory role of cellular miR‐17 in ROS generation through over‐expression and knockdown of miR‐17 in human microglial cells exposed to HIV‐1 Tat C protein. Activated microglial cells mediated neuroinflammatory events are observed in HIV‐associated neurological disorders. The reduction in miR‐17 levels was observed in microglial cells exposed to HIV‐1 Tat C protein. miR‐17 regulated the expression of NOX2 and NOX4, which in turn regulated the reactive oxygen species (ROS) production in microglial cells. Increased ROS production led to the activation of microglial cells and increased cytokine production. This study thus demonstrated a novel miR‐17‐mediated regulatory pathway of ROS production in microglial cells. HMC3 = human microglia clone 3 cell lines. Activated microglial cells mediated neuroinflammatory events are observed in HIV‐associated neurological disorders. The reduction in miR‐17 levels was observed in microglial cells exposed to HIV‐1 Tat C protein. miR‐17 regulated the expression of NOX2 and NOX4, which in turn regulated the reactive oxygen species (ROS) production in microglial cells. Increased ROS production led to the activation of microglial cells and increased cytokine production. This study thus demonstrated a novel miR‐17‐mediated regulatory pathway of ROS production in microglial cells. HMC3 = human microglia clone 3 cell lines.